1997
DOI: 10.1016/s0378-1135(96)01337-5
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus: a persistent infection

Abstract: Persistent infection with porcine reproductive and respiratory syndrome virus (PRRSV) was shown in experimentally infected pigs by isolation of virus from oropharyngeal samples for up to 157 days after challenge. Four 4 week old, conventional, PRRSV antibody-negative pigs were intranasally inoculated with PRRSV (ATCC VR-2402). Serum samples were collected every 2 to 3 days until day 42 post inoculation (PI), then approximately every 14 days until day 213 PI. Fecal samples were collected at the time of serum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
143
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(158 citation statements)
references
References 40 publications
7
143
0
7
Order By: Relevance
“…Selection of samples to be assayed for virus was based on previous reports of persistent infection (Benfield et al, 1997;Wills et al, 1997 (Beaver et al, 2000). Prior to euthanasia, serum, peripheral blood leukocytes, and oropharyngeal scrapings (Wills et al, 1997) were collected.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of samples to be assayed for virus was based on previous reports of persistent infection (Benfield et al, 1997;Wills et al, 1997 (Beaver et al, 2000). Prior to euthanasia, serum, peripheral blood leukocytes, and oropharyngeal scrapings (Wills et al, 1997) were collected.…”
Section: Experimental Designmentioning
confidence: 99%
“…Prior to euthanasia, serum, peripheral blood leukocytes, and oropharyngeal scrapings (Wills et al, 1997) were collected. Following euthanasia, lung, bronchoalveolar lavage, tonsil, and tracheobronchial lymph node samples were collected.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although it was not shown to be transmissible, virus was isolated from oropharyngeal samples of individual pigs for up to 157 days after experimental infection [13]. Nevertheless, virus transmission to susceptible contacts was already shown for up to 56 days after experimental infection [5].…”
Section: Data Processingmentioning
confidence: 99%
“…Persistence can occur when R 1 and new susceptible animals are added to the population at a sufficiently high rate. Although several studies have demonstrated that PRRSV persists in individual pigs [10][11][12][13][14], little is known about PRRSV transmission among pigs [5,15,16] and about its persistence within herds. The objective of this longitudinal study was to investigate the population dynamics of PRRSV infection and to quantify transmission within a breeding herd.…”
Section: Introductionmentioning
confidence: 99%
“…Passively acquired SVN antibody alone was proven to prevent viremia and reproductive failure in pigs challenged with virulent PRRSV strains (Osorio et al, 2002), suggesting the critical role of SVN antibody in the control of virus infection. Nonetheless, cell-mediated immunity (CMI) appears to be essential for the clearance of PRRSV since PRRSV has been detected in lungs and lymph nodes despite the presence of SVN antibodies in serum or bronchoalveloar lavage fluid (Wills et al, 1997;Labarque et al, 2000;Bierk et al, 2001). The mechanisms for the weak induction of protective immunity by PRRSV have been explored in previous studies.…”
Section: Introductionmentioning
confidence: 99%